A versatile communication approach between autonomous vehicles in dynamic environment - ., Sirisha; M.C, Chinnaaiah; M, Anusha.; P, Asharani; Anusha, K (International Journal of Engineering and Technology, 2026)
The current state-of-the-art in wireless communication technology is within vehicles as well as between vehicles.Different concepts associated with radio frequency bands and wave propagation simulations are applied to inter-vehicle communication analysis. The Medium Access Control (MAC) layer protocols used for routing in inter-vehicle communication. Security issues associated with inter-vehicle communication are reviewed.In Proposed communication techniques The push buttons switches are arranged inside the car where the driver presses the buttons, which notify whether the route is busy or not. This data is broadcasted over the internet using node MCU to the other available driver in the next route whether to choose this road are not. In this system ambulance can directly communicate with other vehicles on its route. Within the range of ten meter, ambulance sends the signal to nearest vehicles make drivers to be alert and give the possible way to the ambulance. Communication between the ambulance and vehicles takes place using RF with Microcontroller which is helpful to driver to check the best route, and avoids the Accidental Area.The proposed technique is simulated in keil Micro vision software and implemented on ATMEGA 328.